Layered metal oxide sodium-ion battery and preparation method
Patent Information
- Application Number
- CN202611277156.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0033]本发明解决现有层状金属氧化物钠离子电池倍率性能差、高电压下产气严重、循环寿命短和无法深度充电问题
本发明通过优化正负极浆料配比、明确匀浆及化成工艺参数,精准控制卷绕尺寸,解决层状金属氧化物钠离子电池倍率性能差、高电压下产气严重、循环寿命短及无法深度充电的问题,提升电池电化学性能,且工艺可重复性强,适合规模化量产。
Smart Images

Figure CN123018091A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery technology, specifically to a layered metal oxide sodium-ion battery and its preparation method. Background Technology
[0002] Terminology Explanation: All English letters and abbreviations used in this invention are standard expressions in the battery field, and their specific meanings are as follows: PP: Polypropylene, a commonly used battery separator material with excellent mechanical properties and chemical stability.
[0003] PE: Polyethylene, a commonly used battery separator material, with good insulation and air permeability, suitable for sodium-ion battery systems.
[0004] NaPF6: Sodium hexafluorophosphate, a commonly used electrolyte salt in sodium-ion battery electrolytes, which can provide sodium ion conduction.
[0005] NaClO4: A commonly used electrolyte salt in sodium-ion battery electrolytes, exhibiting excellent ionic conductivity.
[0006] DMC: Dimethyl carbonate, a commonly used organic solvent in electrolytes, characterized by low viscosity and high dielectric constant.
[0007] EC: Ethylene carbonate, a commonly used organic solvent in electrolytes, which can improve the ionic conductivity and stability of electrolytes.
[0008] PC: Propylene carbonate, a commonly used organic solvent in electrolytes, with excellent low-temperature performance, which can broaden the operating temperature range of batteries.
[0009] FEC: Fluorinated ethylene carbonate electrolyte additive, which can form a stable SEI film on the electrode surface, reduce gas production and improve battery cycle performance.
[0010] VC: An electrolyte additive that can improve the density of the SEI film, inhibit electrolyte decomposition, and enhance battery safety.
[0011] SEM: Scanning electron microscope, used to observe the surface morphology and microstructure of battery electrodes, is a material characterization method.
[0012] EDS: Energy Dispersive X-ray Spectrometer, often used in conjunction with SEM, is used to analyze the elemental composition and content of electrode materials, and is a material characterization method.
[0013] XRD: X-ray diffraction, used to analyze the crystal structure of battery cathode materials and determine the phase composition of the materials, is a material characterization method.
[0014] CV: Cyclic voltammetry is used to test the electrochemical performance of batteries and analyze the sodium ion insertion / extraction process and redox reaction characteristics.
[0015] EIS: Electrochemical impedance spectroscopy, used to test the impedance characteristics of a battery, analyze charge transfer impedance, ion diffusion impedance, etc., and evaluate the battery's electrochemical performance.
[0016] SP: Superconducting carbon black, a commonly used conductive agent in batteries, can improve the conductivity of electrodes and promote electron transport.
[0017] PVDF: Polyvinylidene fluoride, a commonly used battery cathode binder, has good adhesion and chemical stability, and is suitable for cathode slurry systems.
[0018] CMC: Sodium carboxymethyl cellulose, a commonly used battery negative electrode binder / thickener that can improve the stability and adhesion of negative electrode slurry.
[0019] SBR: Styrene-butadiene rubber, a commonly used battery negative electrode binder, can enhance the flexibility and bonding strength of the negative electrode sheet. It works even better when used in conjunction with CMC.
[0020] EMC: Ethyl methyl carbonate, a commonly used organic solvent in electrolytes, which can adjust the viscosity and dielectric constant of the electrolyte.
[0021] DEC: Diethyl carbonate, a commonly used organic solvent in electrolytes, which can improve the low-temperature performance and compatibility of electrolytes.
[0022] SOC: State of Charge, the percentage of remaining battery charge, used to characterize the battery's charging state. In this invention, EIS tests are all conducted at 50% SOC to ensure consistent testing conditions.
[0023] C: Battery charge / discharge rate. 1C means the battery can be fully charged and discharged in 1 hour. 0.05C is a small current for slow charging and discharging. 5C and 10C are large currents for high-rate charging and discharging.
[0024] Rct: Charge transfer impedance, which reflects the ease with which sodium ions are transferred at the electrode / electrolyte interface. The lower the Rct value, the better the electrochemical performance of the battery.
[0025] ppm: Parts per million. In this invention, it is used to indicate the moisture content in the battery cell. A value below 200 ppm means that the moisture content is less than 200 parts per million.
[0026] CR2023: The specification of a button cell, where 20 indicates a cell diameter of 20mm and 23 indicates a cell thickness of 2.3mm. It is a commonly used button cell specification in laboratories.
[0027] SEI film: Solid electrolyte interface film, a dense and stable protective film formed on the electrode surface during the first charge and discharge of the battery, which can prevent the continuous decomposition of the electrolyte and improve the battery cycle life and safety.
[0028] In recent years, sodium-ion batteries have developed rapidly with the expansion of market demand, gradually occupying a place in power and energy storage, and are gradually replacing lead-acid batteries in some application scenarios such as two-wheeled vehicles and energy storage.
[0029] Due to fluctuations in raw material prices, the current cost of sodium-ion batteries is not lower than that of lithium iron phosphate batteries, and this price is not expected to fall significantly below that of lithium iron phosphate batteries in the near future. However, considering the actual reserves of both lithium and sodium ion resources, as well as environmental sustainability, the demand for sodium-ion batteries will increase in line with the supply and demand dynamics of lithium resources. The high safety and excellent wide-temperature performance of sodium-ion batteries make them promising for applications in power batteries, large-scale energy storage, and other fields.
[0030] Compared to lithium ions, sodium ions have a larger radius and a slower transport rate within the battery. Their performance is significantly influenced by battery materials, formulation, and structure. Sodium-ion batteries mainly consist of a positive electrode, a negative electrode, a separator, and an electrolyte. The formulation significantly affects the safety performance and cycle life of sodium-ion batteries. Therefore, an ideal battery system requires appropriate formulation design. Positive electrode materials for sodium-ion batteries mainly include layered metal oxides (O3 type, P2 type, tunnel type), polyanionic materials (sodium iron pyrophosphate, sodium iron sulfate, sodium vanadium phosphate, etc.), and Prussian blue materials. Negative electrode materials mainly include hard carbon (biomass-based, sugar-based, resin-based, etc.), soft carbon (petroleum coke, needle coke, anthracite, etc.), titanium-based materials, organic materials, and alloy materials. The electrolyte for sodium-ion batteries is mainly sodium hexafluorophosphate and sodium perchlorate. The current mainstream approach in the market uses layered metal oxides (LMOs) and hard carbon. LMOs, commonly of the O3 type, have high sodium ion content and high initial capacity. However, because sodium ions occupy the center of the octahedron, the diffusion barrier is high, resulting in poor rate performance and capacity retention. LMO materials are typically modified by introducing heteroatoms or ion pairs to alter the cation potential. Theoretically, modified LMOs can achieve charging voltages of 4.2V and above. However, due to their strong alkalinity and the influence of the electrolyte system, the charging voltage of sodium-ion batteries composed of LMOs and hard carbon generally does not exceed 4.1V. Otherwise, under high oxidation states, significant gas production occurs, and early cycle performance declines rapidly. Therefore, the inability to deeply charge these batteries hinders the rapid commercialization of sodium-ion batteries.
[0031] Because of the large ionic radius, the crystal structure of the cathode material in sodium-ion battery systems is unstable during the insertion and extraction process, which may lead to irreversible phase transitions. This has a significant impact on energy density and cycle life. Furthermore, the formation of new interfaces exacerbates internal side reactions and is accompanied by obvious gas production.
[0032] Compared to pouch cells, the cylindrical cell structure can suppress the failure of sodium-ion batteries due to gas production to a certain extent. During long-term cycling, gas production can cause the battery to bulge and increase the internal pressure. Pouch cells pose a safety risk that cannot be avoided in the short term. Therefore, cylindrical sodium-ion batteries currently have great advantages in commercial applications. Summary of the Invention
[0033] This invention solves the problems of poor rate performance, severe gas generation at high voltage, short cycle life, and inability to deeply charge existing layered metal oxide sodium-ion batteries.
[0034] To achieve the above objectives, this invention provides a layered metal oxide sodium-ion battery. The sodium-ion battery comprises a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode uses sodium nickel iron manganese oxide or sodium copper iron manganese oxide as the active material. The negative electrode uses hard carbon, soft carbon, or carbon-free negative electrode as the active material. The separator is a PP, PE, or composite separator. The electrolyte is 1 mol / L NaPF6 or 1 mol / L NaClO4 dissolved in a DMC:EC:PC mixed solvent with a volume ratio of 1:1:1, with 5% FEC and 1% VC added by mass. The sodium-ion battery is a cylindrical sodium-ion battery with a capacity of 18650-1300 mAh and a charge / discharge voltage range of 2.0~4.0V.
[0035] On the other hand, the present invention provides a method for preparing a layered metal oxide sodium-ion battery, comprising the following steps: S1, preparing positive and negative electrode slurries, wherein the positive electrode slurry uses layered metal oxide as the active material, and the negative electrode slurry uses hard carbon, soft carbon or carbon-free negative electrode as the active material, and stirring them evenly according to the corresponding ratios. S2. The positive and negative electrode slurries are coated on the corresponding foil surfaces, and after baking, rolling, slitting, and sheet forming, vacuum baking is performed. S3. The baked positive and negative electrode sheets are wound together with the separator to obtain the battery cell; S4. After inserting the battery cell into the casing and soldering the bottom, vacuum bake it again, then inject liquid, seal, clean, and label it; S5. After sealing, the cells are subjected to high-temperature storage, formation, and room-temperature storage treatments. Batteries with qualified K values are screened to complete the preparation. The materials were characterized using SEM, EDS, and XRD during the preparation process, and their electrochemical performance was tested using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS).
[0036] Further, in step S1, the ratio of the positive electrode slurry is: active material: conductive agent: binder = (90%~98%): (1%~5%): (1%~5%), and the solid content of the positive electrode slurry is 65%±4%. The ratio of the negative electrode slurry is: active material: conductive agent: binder = (90%~97%): (1%~5%): (1%~5%), the binder includes CMC and SBR, the solid content of the negative electrode slurry is 52%±4%, the positive electrode conductive agent is SP, the binder is PVDF, the negative electrode conductive agent is SP, and the binder is a mixture of CMC and SBR. The positive electrode binder ratio is CMC:SBR = (0.5%~3%):(0.8%~4%). The positive electrode slurry mixing process is to use a high-speed disperser to stir at 2000~3000 r / min for 30~60 min, add raw materials in steps, first premix the active material and conductive agent for 10 min, and then add the binder solution and stir until there are no lumps. The negative electrode slurry mixing process is to use a planetary mixer to stir at 1500~2000 r / min for 40~80 min, first dissolve CMC into an aqueous solution, add the active material and conductive agent and stir for 30 min, and then add SBR and stir for 20 min.
[0037] Further, in step S2, the positive electrode foil is aluminum foil or carbon-coated aluminum foil with a thickness of 10-20 μm, and the positive electrode slurry coating surface density is 12-17 mg / cm². The negative electrode foil is aluminum foil, copper foil, or carbon-coated foil, with copper foil having a thickness of 6-15 μm and aluminum foil having a thickness of 10-20 μm. The negative electrode slurry coating surface density is 0.5-1.0 mg / cm². The baking temperature is 60-120℃, and the compaction density of the positive electrode sheet during rolling is 3.0-3.2 g / cm³, and the compaction density of the negative electrode sheet is... The density is 0.9~1.1 g / cm³. After slitting, the width of the positive electrode sheet is 56~58 mm, and the width of the negative electrode sheet is 57~59 mm. During the sheet preparation process, one aluminum tab is welded to the positive electrode, and two nickel tabs, aluminum tabs, or nickel-aluminum composite tabs are continuously welded to the negative electrode. During the vacuum baking, the baking temperature of the positive electrode is 100~130℃, the baking time is 8~24h, and the vacuum degree is ≤-0.09MPa. The baking temperature of the negative electrode is 80~100℃, the baking time is 8~24h, and the vacuum degree is ≤-0.09MPa.
[0038] Furthermore, in step S3, the thickness of the separator is 6~20μm, and during winding, the negative electrode extends 1mm beyond the positive electrode in each direction, and the separator extends 1.2~1.5mm beyond the negative electrode in each direction. The winding structure conforms to the internal structure of a cylindrical sodium-ion battery and is composed of a negative electrode sheet, a separator, and a positive electrode sheet wound sequentially.
[0039] Furthermore, in step S4, the temperature of the second vacuum baking is 60~90℃, the moisture content of the battery cell is less than 200ppm after baking, the dew point of the liquid injection environment is less than -40℃, and after liquid injection, seepage treatment is performed before sealing.
[0040] Further, in step S5, the high-temperature resting temperature is 50°C, the resting time is 40±8h, the formation is performed using a small current of 0.05C, and after formation, it is rested again at 50°C for 40±8h, followed by discharge at 0.2C, and the resting time at room temperature is 72h. Batteries with a K value lower than 0.02mV / h are selected as qualified products. The relative humidity of the environment during the preparation process is controlled to be lower than 10%. The battery cycle test rate is 1C charging and 1C / 5C / 10C discharging.
[0041] Furthermore, after the cell cycle test is completed, it is disassembled in a fully discharged state. The disassembled electrode is soaked and cleaned with organic solvents such as DMC, EMC, or DEC. The cleaned positive electrode is cut into a 12mm diameter circle as the positive electrode of the coin cell. A 14mm self-made sodium sheet is used as the counter electrode of the coin cell. Glass fiber membrane, PP or PE membrane are used, and 1mol / L NaClO4 / (EC:DEC=1:1) electrolyte is used to assemble the CR2023 type coin cell.
[0042] Furthermore, after the button cell is assembled, CV and EIS tests are performed. The CV test voltage range is 2~4V, the scan rate is 0.1mV / s, and the test is performed for three cycles. The EIS test is performed when the battery is at 50% SOC, and the EIS test frequency range is 100KHz~0.001Hz.
[0043] Further, the preferred ratio of the positive electrode slurry is sodium nickel iron manganese oxide: SP: PVDF = 96%: 2%: 2% or 94.5%: 3%: 2.5%, and the preferred solid content is 65% ± 2%. The preferred ratio of the negative electrode slurry is hard carbon: SP: CMC: SBR = (92%~96%): (1%~3%): (0.5%~2.5%): (0.8%~3.5%), and the preferred solid content is 52% ± 2%.
[0044] Compared with known public technologies, the technical solution provided by this invention has the following beneficial effects: This invention addresses the problems of poor rate performance, severe gas generation at high voltage, short cycle life, and inability to deeply charge layered metal oxide sodium-ion batteries by optimizing the ratio of positive and negative electrode slurries, clarifying homogenization and formation process parameters, and precisely controlling the winding size. It improves the electrochemical performance of the battery, and the process is highly repeatable, making it suitable for mass production. Attached Figure Description
[0045] Figure 1 The structure of a cylindrical sodium-ion battery is shown in the diagram, which visually demonstrates the internal winding structure of the cylindrical sodium-ion battery of the present invention and clarifies the positional relationship of each component. The negative electrode 1, the separator 2, and the positive electrode 4 are wound together, and the aluminum foil 1-1 is also shown.
[0046] Figure 2 Capacity retention rate of cylindrical sodium-ion batteries after 500 and 1000 1C charge-discharge cycles.
[0047] Figure 3 EIS for 500 and 1000 1C charge-discharge cycles of cylindrical sodium-ion batteries.
[0048] Figure 4 The images show the SEM results of the positive electrode a, b, and c of a new cylindrical sodium-ion battery after 500 1C charge-discharge cycles and 1000 1C charge-discharge cycles, respectively.
[0049] Figure 5 EDS for positive electrode sheets in different embodiments.
[0050] Figure 6 The first cycle curve of the CV test corresponding to the coin cell assembly of the positive electrode sheet of different embodiments is shown.
[0051] Figure 7 EIS test curves were generated for the positive electrode sheets of different embodiments, corresponding to the coin cells. Detailed Implementation
[0052] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.
[0053] It should be noted that the terms "first," "second," etc., in the specification, claims, and accompanying drawings of this invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments of the invention described herein can be implemented in orders other than those illustrated or described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover a non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.
[0054] The present invention will now be described in further detail with reference to the accompanying drawings: The process for preparing a high-rate, long-cycle NNR18650-1300 sodium-ion battery is as follows: 1. Sodium nickel iron manganese oxide is used as the positive electrode material, hard carbon is used as the negative electrode, and the separator is a 16μm PE base membrane.
[0055] 2. Stir the mixture at 2000~3000r / min for 30~60min using a high-speed disperser, adding the raw materials in steps. First, premix the active material and conductive agent for 10min, then add the binder solution and stir until there are no lumps. Stir sodium nickel iron manganese oxide, SP, and PVDF in a ratio of 96%:2%:2% to form a slurry with a solid content of 65%±2%, and coat it onto the surface of aluminum foil. Then, using a suitable negative electrode homogenization process, stir hard carbon, SP, CMC, and SBR in a ratio of (92%~96%):(1%~3%):(0.5%~2.5%):(0.8%~3.5%) to form a slurry with a solid content of 52%±2%, and coat it onto the surface of aluminum foil.
[0056] 3. The coating surface density of the positive electrode is 12~17 mg / cm², and that of the negative electrode is 0.5~1.0 mg / cm².
[0057] 4. The designed electrode structure features a single welded tab for the positive electrode and continuously welded double tabs for the negative electrode. During battery manufacturing, the relative humidity of the environment is controlled to be below 10%.
[0058] 5. After winding, the battery cell is baked at a temperature of 60~90℃, and the moisture content after baking is below 200ppm.
[0059] 6. After sealing, place the battery cell in a high-temperature chamber for 40±8 hours. After forming with a small current of 0.05C, place it back in the high-temperature chamber for 40±8 hours and discharge at 0.2C.
[0060] 7. After being placed at high temperature for 72 hours and at room temperature for 72 hours, measure the K value. Batteries with lower K values are used for testing.
[0061] Prepare cylindrical batteries for 500 and 1000 cycles: Take three batteries of each type and perform 1C charge-discharge cycles, setting them to 500 and 1000 cycles respectively. After the cycles are completed, test the EIS of the new batteries, the 500-cycle, and the 1000-cycle cylindrical batteries respectively.
[0062] Example 1: Sodium nickel iron manganese oxide, SP, and PVDF are mixed in a ratio of 96%:2%:2% to form a slurry with a solid content of 65%±4% and a coating density of 17mg / cm². The slurry is coated on the surface of aluminum foil, and after being rolled with a compaction density of 3.0g / cm³, the electrode sheet is slit and aluminum tabs are welded on.
[0063] Hard carbon, SP, CMC, and SBR are mixed in a ratio of 96%:1%:1%:2% to form a slurry with a solid content of 52%±4%. The coating surface density is 1.0 mg / cm². The slurry is coated on the surface of aluminum foil, and after being compacted by roller pressing at 0.9 g / cm³, the electrode sheet is slit and nickel tabs are welded on.
[0064] like Figure 1 As shown, the prepared positive and negative electrode sheets are wound.
[0065] The wound battery cells are placed into the casing, the bottom is soldered, and then baked at 80°C for 48 hours.
[0066] After baking, place the battery cells in an environment with a dew point of less than -40°C for electrolyte injection. Once the electrolyte seepage is complete, promptly weld on the caps and seal the cells. Clean the electrolyte and apply labels.
[0067] After the battery cells have been filled with electrolyte, they are placed at 50°C for 48 hours, formed with a small current of 0.05C, and then placed back in a high-temperature chamber for 48 hours and discharged at 0.2C.
[0068] Batteries that are left at 50℃ for 72 hours, and then left at room temperature for 72 hours, with a K value below 0.02mV / h are used for testing.
[0069] Prepare three new cylindrical batteries and test the EIS of each battery separately. Figure 3 As shown.
[0070] After fully discharging the batteries with good consistency, disassemble them and obtain SEM images of the positive electrode, such as... Figure 4 As shown, an EDS test was performed on it, and the test results are as follows. Figure 5 As shown.
[0071] After wiping one side of the electrode, it was vacuum baked at 80℃ for 12 hours and cut into 12mm diameter round pieces. Then, the coin cell was assembled in a glove box. The coin cell assembly used a 14mm self-made sodium sheet as the counter electrode of the coin half cell, with a glass fiber diaphragm and a 1mol / L NaClO4 / (EC:DEC=1:1) electrolyte.
[0072] The positive electrode homogenization process corresponds to claim 3, employing a high-speed disperser at 2000~3000 r / min for 30~60 min, with stepwise premixing. The conditions for performing CV testing on the assembled button cell are: 1) Let it stand at room temperature for more than 20 hours; 2) The voltage range used is 2~4V; 3) Sweep speed 0.1 mV / s; 4) Direction: Forward scan; 5) Test three laps.
[0073] like Figure 6 As shown, the CV curves are displayed for different number of cycles, and the first cycle curve is separated.
[0074] Test EIS at 50% SOC, test frequency: 100kHz~0.001Hz, such as... Figure 7 As shown, the capacitance of the coin cell is tested at a rate of 0.1C and a voltage range of 2~4V. The capacitance of the first cycle is recorded.
[0075] Example 2: Sodium nickel iron manganese oxide, SP, and PVDF were mixed in a ratio of 94.5%:3%:2.5% to form a slurry with a solid content of 65%±4% and a coating density of 17mg / cm². The slurry was coated on the surface of aluminum foil, and after being rolled with a compaction density of 3.0g / cm³, the electrode sheet was slit and aluminum tabs were welded on.
[0076] The other battery manufacturing processes were the same as in Example 1. The batteries were then subjected to capacity testing to prepare three new cylindrical batteries. The EIS of each cylindrical battery was tested. Figure 3 As shown, the electrode was disassembled and soaked for cleaning, the coin cell was assembled, and the coin cell CV and specific capacity were tested under the same conditions as in Example 1.
[0077] Comparative Example 1: Sodium nickel iron manganese oxide, SP, and PVDF were mixed in a ratio of 96%:2%:2% to form a slurry with a solid content of 65%±4% through a positive electrode homogenization process. The coating surface density was 17mg / cm². The slurry was coated on the surface of aluminum foil, and after being rolled with a compaction density of 3.0g / cm³, the electrode sheet was slit and aluminum electrode tabs were welded on.
[0078] The other battery manufacturing processes were the same as in Example 1. After the batteries underwent formation and capacity testing, and were cycled 500 times, the EIS of the cylindrical batteries was tested. Figure 3 As shown, the electrode sheets were disassembled, soaked, and cleaned. The coin cell was then assembled, and its CV and specific capacity were tested under the same conditions as in Example 1. Figure 6 and Figure 7 The CV curve and EIS are for Comparative Example 1.
[0079] Comparative Example 2: Sodium nickel iron manganese oxide, SP, and PVDF were mixed in a ratio of 94.5%:3%:2.5% to form a slurry with a solid content of 65%±4% and a coating density of 17mg / cm². The slurry was coated on the surface of aluminum foil, and after being rolled with a compaction density of 3.0g / cm³, the electrode sheet was slit and aluminum tabs were welded on.
[0080] The other battery manufacturing processes were the same as in Example 1. After the batteries underwent formation and capacity testing, and were cycled 500 times, the EIS of the cylindrical batteries was tested. Figure 3 As shown, the electrode was disassembled and soaked for cleaning, the coin cell was assembled, and the coin cell CV and specific capacity were tested under the same conditions as in Example 1. Figure 6 and Figure 7 The CV curve and EIS are for Comparative Example 2.
[0081] Comparative Example 3: Sodium nickel iron manganese oxide, SP, and PVDF were mixed in a ratio of 96%:2%:2% to form a slurry with a solid content of 65%±4% through a positive electrode homogenization process. The coating surface density was 17mg / cm². The slurry was coated on the surface of aluminum foil, and after being rolled with a compaction density of 3.0g / cm³, the electrode sheet was slit and aluminum electrode tabs were welded on.
[0082] The other battery manufacturing processes are the same as in Example 1. The batteries are then subjected to capacity testing. Three cylindrical batteries are taken and each undergoes a 1C charge-discharge cycle, set to 1000 cycles. The cycle capacity retention rate is as follows: Figure 2 As shown, the EIS of cylindrical batteries were tested respectively. Figure 3 As shown, the electrode was disassembled and soaked for cleaning, the coin cell was assembled, and the coin cell CV and specific capacity were tested under the same conditions as in Example 1. Figure 6 and Figure 7 The CV curve and EIS are for Comparative Example 3.
[0083] Comparative Example 4: Sodium nickel iron manganese oxide, SP, and PVDF were mixed in a ratio of 94.5%:3%:2.5% to form a slurry with a solid content of 65%±4% and a coating density of 17mg / cm². The slurry was coated on the surface of aluminum foil, and after being rolled with a compaction density of 3.0g / cm³, the electrode sheet was slit and aluminum tabs were welded on.
[0084] The other battery manufacturing processes are the same as in Example 1. The batteries are then subjected to capacity testing. Three cylindrical batteries are taken and each undergoes a 1C charge-discharge cycle, set to 1000 cycles. The cycle capacity retention rate is as follows: Figure 2 As shown, the EIS of cylindrical batteries were tested respectively. Figure 3 As shown, the electrode sheets were disassembled, soaked, and cleaned. The coin cell was then assembled, and its CV and specific capacity were tested under the same conditions as in Example 1. Figure 6 and Figure 7 The CV curve and EIS are for Comparative Example 4.
[0085] Comparative Example 5: Sodium nickel iron manganese oxide, SP, and PVDF were mixed in the corresponding proportions to form a slurry with a solid content of 65% ± 4% by a positive electrode homogenization process. The coating surface density was 17 mg / cm². The slurry was coated on the surface of aluminum foil, and after being rolled with a compaction density of 3.0 g / cm³, the electrode sheet was slit and aluminum electrode tabs were welded on.
[0086] The other battery manufacturing processes are the same as in Example 1. The batteries are then subjected to capacity testing. Three cylindrical batteries are taken and subjected to 1C charge-discharge cycles, set to 1500 cycles. The cycle capacity retention rate is as follows: Figure 2 As shown, the EIS of cylindrical batteries were tested respectively. Figure 3 As shown, the electrode sheets were disassembled, soaked, and cleaned. The coin cell was then assembled, and its CV and specific capacity were tested under the same conditions as in Example 1. Figure 6 and Figure 7 To correspond to the CV curve and EIS of the scale.
[0087] Comparative Example 6: Sodium nickel iron manganese oxide, SP, and PVDF were mixed in a ratio of 94.5%:3%:2.5% to form a slurry with a solid content of 65%±4% and a coating density of 17mg / cm². The slurry was coated on the surface of aluminum foil, and after being rolled with a compaction density of 3.0g / cm³, the electrode sheet was slit and aluminum tabs were welded on.
[0088] The other battery manufacturing processes are the same as in Example 1. The batteries are then subjected to capacity testing. Three cylindrical batteries are taken and subjected to 1C charge-discharge cycles, set to 1500 cycles. The cycle capacity retention rate is as follows: Figure 2 As shown, the EIS of cylindrical batteries were tested respectively. Figure 3 As shown, the electrode sheets were disassembled, soaked, and cleaned. The coin cell was then assembled, and its CV and specific capacity were tested under the same conditions as in Example 1. Figure 6 and Figure 7 The CV curve and EIS are for Comparative Example 6.
[0089] Table 1 shows the comparison data of full-charge Rct (at 50% SOC) and half-charge 0.1C capacity retention for different embodiments and comparative examples: Example 1 0.0127 100% Comparative Example 1 0.04 80% Comparative Example 3 0.069 75% Comparative Example 5 0.45 30% Example 2 0.0078 100% Comparative Example 2 0.021 89% Comparative Example 4 0.034 88% Comparative Example 6 0.088 71%
[0090] In summary, this invention provides an electrochemical analysis of the gradual failure mechanism of gas generation during cycling in cylindrical sodium-ion batteries, establishing a correlation between cathode materials and battery cycle life. This allows researchers to optimize the material structure stability and improve battery cycle performance. Furthermore, the batteries prepared in Examples 1 and 2 exhibit 100% specific capacity retention in the new battery state and slow performance degradation during cycling, significantly outperforming the comparative example. The Rct of Example 2 is only 0.0078 mΩ, significantly lower than that of the comparative example, indicating that the process of this invention can effectively reduce charge transfer impedance and possesses excellent commercial application potential.
[0091] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A layered metal oxide sodium-ion battery, characterized in that, The sodium-ion battery consists of a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode uses sodium nickel iron manganese oxide or sodium copper iron manganese oxide layered metal oxide as the active material. The negative electrode uses hard carbon, soft carbon, or carbon-free negative electrode as the active material. The separator is PP, PE, or a composite separator. The electrolyte is 1 mol / L NaPF6 or 1 mol / L NaClO4 dissolved in a DMC:EC:PC mixed solvent with a volume ratio of 1:1:1, and 5% FEC and 1% VC are added by mass. The sodium-ion battery is a cylindrical sodium-ion battery with a capacity of 18650-1300mAh and a charge / discharge voltage range of 2.0~4.0V.
2. A method for preparing a layered metal oxide sodium-ion battery, applied to the layered metal oxide sodium-ion battery of claim 1, characterized in that, Includes the following steps: S1. Prepare positive and negative electrode slurries. The positive electrode slurry uses layered metal oxides as active materials, and the negative electrode slurry uses hard carbon, soft carbon or carbon-free negative electrode as active materials. Stir them evenly according to the corresponding ratios. S2. The positive and negative electrode slurries are coated on the corresponding foil surfaces, and after baking, rolling, slitting, and sheet forming, vacuum baking is performed. S3. The baked positive and negative electrode sheets are wound together with the separator to obtain the battery cell; S4. After inserting the battery cell into the casing and soldering the bottom, vacuum bake it again, then inject liquid, seal, clean, and label it; S5. After sealing, the cells are subjected to high-temperature storage, formation, and room-temperature storage treatments. Batteries with qualified K values are screened to complete the preparation. The materials were characterized using SEM, EDS, and XRD during the preparation process, and their electrochemical performance was tested using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS).
3. The method for preparing a layered metal oxide sodium-ion battery according to claim 2, characterized in that, In step S1, the positive electrode slurry has the following composition: active material: conductive agent: binder = (90%~98%): (1%~5%): (1%~5%), and the solid content of the positive electrode slurry is 65%±4%. The negative electrode slurry has the following composition: active material: conductive agent: binder = (90%~97%): (1%~5%): (1%~5%), and the binder includes CMC and SBR. The solid content of the negative electrode slurry is 52%±4%. The positive electrode conductive agent is SP, the binder is PVDF, the negative electrode conductive agent is SP, and the binder is a mixture of CMC and SBR. The agent ratio is CMC:SBR = (0.5%~3%):(0.8%~4%). The positive electrode slurry stirring process is to use a high-speed disperser to stir at 2000~3000 r / min for 30~60 min, add raw materials in steps, first premix the active material and conductive agent for 10 min, then add the binder solution and stir until there are no lumps. The negative electrode slurry stirring process is to use a planetary mixer to stir at 1500~2000 r / min for 40~80 min, first dissolve CMC into an aqueous solution, add the active material and conductive agent and stir for 30 min, then add SBR and stir for 20 min.
4. The method for preparing a layered metal oxide sodium-ion battery according to claim 2, characterized in that, In step S2, the positive electrode foil is aluminum foil or carbon-coated aluminum foil with a thickness of 10-20 μm, and the positive electrode slurry coating surface density is 12-17 mg / cm². The negative electrode foil is aluminum foil, copper foil, or carbon-coated foil, with copper foil having a thickness of 6-15 μm and aluminum foil having a thickness of 10-20 μm. The negative electrode slurry coating surface density is 0.5-1.0 mg / cm². The baking temperature is 60-120℃, and the compaction density of the positive electrode sheet during rolling is 3.0-3.2 g / cm³, and the compaction density of the negative electrode sheet is... The content is 0.9~1.1 g / cm³. After slitting, the width of the positive electrode sheet is 56~58 mm, and the width of the negative electrode sheet is 57~59 mm. During the sheet preparation process, one aluminum tab is welded to the positive electrode, and two nickel tabs, aluminum tabs, or nickel-aluminum composite tabs are continuously welded to the negative electrode. During the vacuum baking, the baking temperature of the positive electrode is 100~130℃, the baking time is 8~24h, and the vacuum degree is ≤-0.09MPa. The baking temperature of the negative electrode is 80~100℃, the baking time is 8~24h, and the vacuum degree is ≤-0.09MPa.
5. The method for preparing a layered metal oxide sodium-ion battery according to claim 2, characterized in that, In step S3, the thickness of the separator is 6~20μm. During winding, the negative electrode extends 1mm beyond the positive electrode in each direction, and the separator extends 1.2~1.5mm beyond the negative electrode in each direction. The winding structure conforms to the internal structure of a cylindrical sodium-ion battery and is composed of a negative electrode sheet, a separator, and a positive electrode sheet wound sequentially.
6. The method for preparing a layered metal oxide sodium-ion battery according to claim 5, characterized in that, In step S4, the temperature of the second vacuum baking is 60~90℃, the moisture content of the battery cell is less than 200ppm after baking, the dew point of the liquid injection environment is less than -40℃, and after liquid injection, seepage treatment is performed before sealing.
7. The method for preparing a layered metal oxide sodium-ion battery according to claim 6, characterized in that, In step S5, the high-temperature resting temperature is 50°C, the resting time is 40±8h, the formation is performed using a small current of 0.05C, and after formation, it is rested again at 50°C for 40±8h, followed by discharge at 0.2C, and the resting time at room temperature is 72h. Batteries with a K value lower than 0.02mV / h are selected as qualified products. The relative humidity of the environment is controlled to be lower than 10% during the preparation process. The battery cycle test rate is 1C charging and 1C / 5C / 10C discharging.
8. The method for preparing a layered metal oxide sodium-ion battery according to claim 2, characterized in that, After the cell cycle test is completed, it is disassembled in a fully discharged state. The disassembled electrode is soaked and cleaned with organic solvents such as DMC, EMC or DEC. The cleaned positive electrode is cut into a 12mm diameter circle as the positive electrode of the coin cell. A 14mm self-made sodium sheet is used as the counter electrode of the coin cell. Glass fiber membrane, PP or PE membrane are used, and 1mol / L NaClO4 / (EC:DEC=1:1) electrolyte is used to assemble the CR2023 type coin cell.
9. The method for preparing a layered metal oxide sodium-ion battery according to claim 8, characterized in that, After the button cell is assembled, CV and EIS tests are performed. The CV test voltage range is 2~4V, the scan rate is 0.1mV / s, and the test is performed for three cycles. The EIS test is performed when the battery is at 50% SOC, and the EIS test frequency range is 100KHz~0.001Hz.
10. The method for preparing a layered metal oxide sodium-ion battery according to claim 3, characterized in that, The preferred ratio of the positive electrode slurry is sodium nickel iron manganese oxide: SP: PVDF = 96%: 2%: 2% or 94.5%: 3%: 2.5%, with a solid content preferably of 65% ± 2%. The preferred ratio of the negative electrode slurry is hard carbon: SP: CMC: SBR = (92%~96%): (1%~3%): (0.5%~2.5%): (0.8%~3.5%), with a solid content preferably of 52% ± 2%.